Al-'Arabiyyah wa al-Islam - Afifah, Iffah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2018)
The purpose of this writing is to encourage and motivate students and teachers to recognize that the Arabic language is among the most important subjects that the global and Islamic communities need to study. It has been a primary component of the curriculum among early scholars because of its close connection to the Qur’an, the Sunnah, Islam, and Islamic sciences. Both classical and contemporary scholars, as well as Orientalists, have acknowledged this fact and greatly benefited from its unique features and significant advantages. Moreover, the Arabic language plays a major role in shaping global civilization and driving social change. Therefore, learning languages—particularly Arabic—has become extremely important for every learner and teacher, whether at an elementary level or through advanced and in-depth study. It is essential to include it in the academic curriculum.